Applied calculus - Taylor, Claudia; Gilligan, Lawrence (California : Brooks/Cole Publishing Company, 1985)
Historically, textbooks for courses in applied calculus were not much more than "watered down" traditional calculus texts $1 (Bbooks originally written for mathematics and engineering students.s
Includes index.
Keywords: CALCULUS